2019
DOI: 10.4183/aeb.2019.86
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and their Association with Obesity: a Cross-Sectional Study

Abstract: Context. Scarce data on dietary habits in Eastern European countries is available and reports investigated individual food items and not dietary patterns in these populations Objective. To identify dietary patterns and to explore their association with obesity in a sample from Romanian population. Design. Cross-sectional. Subjects and Methods. This was an analysis of data collected from 1398 adult participants in ORO study. Data on lifestyle, eating habits and food frequency consumption were collected. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
4
22
0
7
Order By: Relevance
“…In this study, while six factors (patterns) had an eigenvalue > 1, only three were above the breaking point in the scree plot and were retained in the analysis. Previous studies have also used the point of inflection in the scree plot, in addition to an eigenvalue greater than one, in deciding on the number of factors to be retained (64)(65)(66). Similar to the results of this study, such an approach yielded a fewer number of factors to be retained as compared to relying solely on the criteria related to the eigenvalue.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, while six factors (patterns) had an eigenvalue > 1, only three were above the breaking point in the scree plot and were retained in the analysis. Previous studies have also used the point of inflection in the scree plot, in addition to an eigenvalue greater than one, in deciding on the number of factors to be retained (64)(65)(66). Similar to the results of this study, such an approach yielded a fewer number of factors to be retained as compared to relying solely on the criteria related to the eigenvalue.…”
Section: Discussionsupporting
confidence: 54%
“…Dietary pattern analysis has been proposed as a better approach in assessing diet quality than a single nutrient or food group. Many studies have been conducted to investigate the association between dietary patterns and obesity [ 10 , 11 , 12 , 13 , 14 ]. A meta-analysis of 18 studies conducted in both Western and Asian populations reported that higher adherence to a Prudent diet was associated with a 36% (OR = 0.64; 95% CI: 0.52, 0.78) lower odds of being overweight or obese [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos recentes sobre padrões alimentares realizados em vários países têm mostrado que padrões mais saudáveis estão associados a menores chances de excesso de peso e obesidade. (EGG et al, 2019;JAYASINGHE et al, 2019;PENG et al, 2019;ROMAN et al, 2019). Em contrapartida, alguns estudos mostram que após o ajuste por covariáveis, a associação de padrões alimentares saudáveis com excesso de peso foi positiva, e que possivelmente as recomendações para diminuição do consumo de alimentos processados, gorduras ou açúcares pelos profissionais de saúde e o avanço nas políticas públicas para elaboração de guias alimentares podem estar contribuindo para que indivíduos com diagnóstico de obesidade abdominal diminuam o consumo desses alimentos.…”
Section: Padrões Alimentaresunclassified
“…O quadro 3 mostra a classificação dos grupos de alimentos para a segunda avaliação dos adultos. As nomeações das classificações de aderência aos padrões alimentares tem respaldo na literatura, onde o termo "Prudente" é geralmente caracterizado por uma alimentação rica em frutas, vegetais e alimentos naturais (ROMAN et al, 2019;TUCKER et al, 2015); o termo "Risco" relata uma alimentação rica em gorduras saturadas e alimentos industrializados (NERI-SÁNCHEZ et al, 2018), e o termo "Misto" é caracterizado por uma alimentação composta tanto de alimentos naturais, como frutas e vegetais, quanto alimentos de industrializados como fast foods e afins.…”
Section: Padrões Alimentares Dos Adultos No Segundo Momento (T2)unclassified
See 1 more Smart Citation